The Self-Governance Shift: Reposisi Etika Profesi Akuntansi dalam Ekosistem Work from Anywhere - Sanditha, Fidia; Zahra, Nabilah Amalia; Aurelia, Dini; Yusnaini, Yusnaini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The transition toward a Work From Anywhere (WFA) ecosystem has triggered a fundamental